Dietary intakes among South Asian adults differ by length of residence in the USA. Issue 2 (20th May 2015) - Talegawkar, Sameera A; Kandula, Namratha R; Gadgil, Meghana D; Desai, Dipika; Kanaya, Alka M
Abstract: Objective: To examine whether nutrient and food intakes among South Asian adult immigrants differ by length of residence in the USA. Design: Cross-sectional analysis to examine differences in nutrient and food intakes by length of residence in the USA. Dietary data were collected using an interviewer-administered, culturally appropriate FFQ, while self-reported length of residence was assessed using a questionnaire and modelled as tertiles. Setting: The Mediators of Atherosclerosis in South Asians Living in America (MASALA) study. Subjects: Eight hundred and seventy-four South Asians (mean age=55 (sd 9) years; 47 % women; range of length of residence in the USA=2–58 years), part of the baseline examination of the MASALA study. Results: Intakes of fat, including saturated and trans fats, dietary cholesterol and n -6 fatty acids, were directly associated with length of residence, while intakes of energy, carbohydrate, glycaemic index and load, protein, dietary fibre, folate and K were inversely associated with length of residence ( P trend <0·05). A longer length of residence in the USA was also associated with higher intakes of alcoholic beverages, mixed dishes including pizza and pasta, fats and oils, and lower intakes of beans and lentils, breads, grains and flour products, milk and dairy products, rice, starchy vegetables and sugar, candy and jam ( P for differences across groups <0·05). Conclusions: Length of residence in the USA influences diet and nutrient intakes among South Asian adult immigrants and should be considered when investigating and planning dietary interventions to mitigate chronic disease risk.